Holocene environmental history at the treeline in the Northern Apennines, Italy: A micromorphological approach. (April 2014) - Compostella, Chiara; Mariani, Guido Stefano; Trombino, Luca
The aim of this work is to investigate paleoenvironment at treeline quotas through the help of soil micromorphology. It also assesses how the micromorphological approach can provide information in paleoenvironmental studies where paleosols are available as proxy archives. Nine soil profiles are described across the treeline, between 1723 and 1860 m, on Mt Cusna slope (2121 m a.s.l., Northern Apennines, Italy). Undisturbed samples from selected soil horizons are collected in Kubiëna boxes. From field observations, all the profiles appear to be composed of two main pedogenetic units: the upper one, composed of a recent soil of colluvial origin, and the deeper one, consisting of an underlying more developed buried paleosol. Thin sections give detailed information about the nature and the origin of both pedological units. Four principal phases of paleosol development are detected. A first period of temperate climate with forest cover and contrasted seasons is followed by a phase of change and then by a successive decrease of forest cover. In a last phase, the soil experiences frost action under the effect of a colder climate. The final deposition of colluvium seems to be very recent (historical time). Moreover, multiple colluvial layers are identified. Colluvial material of different origins could be identified as part of dismantled soils similar to the preexisting paleosol. In conclusion, with the help of soil micromorphology, it is possible to assess the existence of past stable forest at least 100 m above the present treeline. The micromorphological approach represents a powerful tool in multidisciplinary paleoenvironmental studies due to its high level of resolution in outlining the individual and successive phases of soil evolution.